A protocol for mobilising novel finance models for collaborative health promotion and disease prevention initiatives: taking a smart capacitating investment approach in the Invest4Health project - Lane, Joanna; Edwards, Rhiannon T.; Babarczy, Balázs; Whiteley, Holly; Oruganti, Vidya; Rutten-van Mölken, Maureen; Costongs, Caroline; Jani, Anant; Wordsworth, Sarah; Maassen, Alison; Tsiachristas, Apostolos; Davies, Jacob; et al. (Frontiers in Public Health, 2024)
BackgroundThe prevalence of preventable non-communicable disease (NCD) underpins the need for a life-course and cross-sectoral approach to population health that is grounded in health promotion and disease prevention. European Union (EU) countries typically spend 6 to 13% of gross domestic product (GDP) on health care, yet less than 3% of this is dedicated to prevention. The extent to which spending in other sectors prevents avoidable ill-health is largely unknown. The lack of fiscal space post-COVID-19 means shifting from models of care built around treatment to those with greater emphasis on prevention will require innovative, evidence-based investment within and between sectors. The term “smart capacitating investment” (SCI) has previously been used to understand how to best boost social infrastructure investment in education, health, transport and housing across the EU. Here we take that idea further by exploring the applicability of SCI to public health financing to improve population health and well-being.AimTo explore and develop innovative SCI models and tools that enable collaboration and investment across health ecosystems for enhanced health promotion and disease prevention, test them in diverse real-world settings, and create a roadmap for large-scale implementation.MethodsThe Invest4Health (I4H) project brings together transdisciplinary expertise in epidemiology, public health, health economics, population science, business management, finance, implementation and social sciences, digital health innovation, and regional health systems. The project consists of eight work packages which span the exploration and conceptualisation of SCI in public health; the characterisation of SCI-compatible business and finance models; piloting and evaluation of these models in four European testbeds (Sweden, Germany, Spain and Wales UK); and exploring the opportunities for sustainable replication and scaling of SCI and future research.DiscussionWe present an introduction to the I4H project, the concept of SCI applied to public health, plus key points for discussion internationally.